The development of methods for determining vibration stochastic fields of technological complexes - Marchenko, Nadiia; Monchenko, Olena; Martyniuk, Ganna (Eastern-European Journal of Enterprise Technologies, 2019)
The force effects occurring in technological complexes have been studied on the basis of the analysis of technical diagnostics system. Due to the distinction between deterministic and random force effects, there have been proposed various methods to distinguish the vibration of informational diagnostic characteristics in order to ensure prompt and reliable detection of the rapidly developing defects. Reliable diagnostics will make it possible to switch from a system of scheduled preventive repairs to the organization of repairs for the current state, with a decrease in the cost of repairing and rebuilding the units of technological complexes by early detection of the defects emerging in the assembly components. On the basis of analyzing the process of propagation of vibroacoustic waves caused by the power action, there has been developed a mathematical model for the emergence and propagation of elastic waves in sophisticated technological complexes from the places of their origin to the point of observation. There have been suggested kinematic schemes for propagation of low-frequency vibrations, vibrosignals from the brush-collector unit, as well as waves from the inner ring of the bearing. This makes possible to substantiate a mathematical model of the occurrence and propagation of vibroacoustic waves in the parts and units of technological complexes from various sources of vibration. The comparative analysis of the research findings on the real vibration fields and the results of numerical modeling confirms the adequacy of the model to the real process. The article presents the graphs of the temporal realization of signals in the model, the spectra of the realized signals, as well as their autocorrelation functions reflecting the main characteristics of the signals at the measurement point. The findings can be used to diagnose and reduce the cost of repair and restoration of the units in sophisticated technological complexes by early detection of the defects emerging in the assembly parts.